EFFECTS OF MELT TEMPERATURE ON THE MAGNETIC-PROPERTIES OF FECUNBSIB ALLOY - LIM, SH; PI, WK; NOH, TH; KIM, HJ; KANG, IK (AMER INST PHYSICS, 1993)
The magnetic properties of an Fe73.5Cu1Nb3Si13.5B9 alloy with nanoscale crystalline structure have been investigated as a function of the melt temperature. In the temperature range of 1240 to 1380-degrees-C investigated in the present study, the permeability increases with the melt temperature. This result may be explained in terms of the reduction in the magnetic anisotropy as a function of the melt temperature. This is supported by the results for the remanence ratio, which also increases with melt temperature in a similar manner to the permeability. In the latter part of the work described in this paper, the relationships between the permeability and the coercivity, and the permeability and the remanence ratio have been investigated for the nanocrystalline alloy. It was found that the permeability is correlated more closely to the remanence ratio than the coercivity.
Keywords: ULTRAFINE GRAIN-STRUCTURE; NANOCRYSTALLINE FERROMAGNETS; B ALLOYS; SI-B; PHASE